IMPLEMENTASI PERKAWINAN SEDARAH PADA MASYARAKAT DESA SEROMBOU INDAH KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Suryani '; Hayatul Ismi; Maryati Bachtiar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Marriage is one of the most important events in human life. Indonesian people who still hold firm customs also know the term "Indigenous Marriage". Indigenous marriage is a very important event in the life of indigenous peoples, because the marriage is not only about the two brides, the two families, but also concerning the community even concerning the spirits of the ancestors of both sides. Regarding marriage is regulated in Law Number 1 Year 1974 About Marriage. Regarding the prohibition of marriage is regulated in Article 8 of the Act. The notion of inbreeding on indigenous peoples Serombou Indah Village, Rambah Hilir sub-district of Rokan Hulu, is different from the notion of inbreeding marriage contained in Article 8 of the Marriage Law. For the indigenous people of Serombou Indah Village which is said to be marriage of inbreeding that is marriage that happened between siblings, father's sister, sister of mother, sister of grandfather.In the village of Serombou Indah there are couples who marry inbreed according to custom. The author then raised the problem into the writing of this thesis. The problem found by the author is that there is an inbreeding between the couple with the initials R and D (initials). Marriage conducted by R and D has violated the custom, because according to the customary law of this area between R and D still have blood relation. The blood relationship between R and D is a brother with a third generation, who is legally prohibited from marriage.Keywords: Marriage, Custom, Marriage.